Implementation of the Muri-Q Qur’an Memorization Method in Increasing Student Motivation and Learning Outcomes - Maskanah, Ulfa; Ulum, Muhammad Samsul; Isroqunnajah, Isroqunnajah; Azzahra, Fatimah; Umur, Muhammad Ma’aliyal (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to describe and analyze the integration of gender perspectives and environmental values ??in Islamic Religious Education (PAI) learning in madrasas. Issues of gender inequality and ecological damage are contemporary challenges that demand a response in Islamic education that remains relevant and contextual. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis was conducted using the Miles & Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that gender integration in PAI has begun to be seen through increased teacher understanding of the principle of equality in Islam and efforts to present representation of female figures in learning materials. However, patriarchal bias is still apparent in practices and teaching materials, so a more systematic strengthening of gender perspectives is needed. In the environmental aspect, madrasas have implemented ecological programs such as Clean Friday, waste banks, reforestation, and energy saving campaigns. Ecological values ??are integrated through the concept of khalifah fil-ardh, environmental fiqh, and the habituation of worship oriented towards nature conservation. The integrative learning strategies implemented by teachers include an integrative thematic approach, project-based learning, reflection (contemplation and reflection), and role models (uswah hasanah) which have been proven effective in increasing gender literacy, ecological awareness, strengthening social morals, and developing 21st-century skills such as creativity, collaboration, and critical thinking.